تطبيقات المقابلة العيادية - مقراني، سهيلة; جابر، نصر الدين (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاجتماعية والانسانية, 2022)
يحاول هذا المقال أن يناقش مسألة مجالات تطبيق المقابلة العيادية ومدى حدودها في تشخيص الاضطرابات النفسية، حيث لا يمكن أن تخلو أي محاولة في التشخيص أو الفحص النفسي من استخدام تقنية المقابلة العيادية، وذلك نظرا لما تتميز به من الخصائص التي تأهلها لأن تكون من بين أهم أدوات جمع المعلومات فقد حاولنا من خلال مقالنا هذا معرفة أهم استخدامات وتطبيقات المقابلة العيادية ومدى إمكانياتها في التشخيص وجمع المعلومات. This article attempts to discuss the issue of the application of clinical interview, and the extent of its limitations in diagnosing psychiatric disorders, where no attempt at diagnosis or psychological examination can be free from the use of the clinical interview technique, this is because of its characteristics that qualify it to be among the most important tools for gathering information, we have tried through this article to know the most important uses and applications of the clinical interview and its capabilities in diagnosing and collecting information.
Keywords: الاضطرابات النفسية -- الفحص العيادي -- العلاج النفسي